Molecular Mapping of Flowering Time Major Genes and QTLs in Chickpea (Cicer arietinum L.) - Mallikarjuna, Bingi P.; Samineni, Srinivasan; Thudi, Mahendar; Sajja, Sobhan B.; Khan, Aamir W.; Patil, Ayyanagowda; Viswanatha, Kannalli P.; Varshney, Rajeev K.; Gaur, Pooran M. (Frontiers in Plant Science, 2017)
Flowering time is an important trait for adaptation and productivity of chickpea in the arid and the semi-arid environments. This study was conducted for molecular mapping of genes/quantitative trait loci (QTLs) controlling flowering time in chickpea using F2 populations derived from four crosses (ICCV 96029 × CDC Frontier, ICC 5810 × CDC Frontier, BGD 132 × CDC Frontier and ICC 16641 × CDC Frontier). Genetic studies revealed monogenic control of flowering time in the crosses ICCV 96029 × CDC Frontier, BGD 132 × CDC Frontier and ICC 16641 × CDC Frontier, while digenic control with complementary gene action in the cross ICC 5810 × CDC Frontier. The intraspecific genetic maps developed from these crosses consisted 75, 75, 68 and 67 markers spanning 248.8 cM, 331.4 cM, 311.1 cM, and 385.1 cM, respectively. A consensus map spanning 363.8 cM with 109 loci was constructed by integrating four genetic maps. Major QTLs corresponding to flowering time genes efl-1 from ICCV 96029, efl-3 from BGD 132 and efl-4 from ICC 16641 were mapped on CaLG04, CaLG08 and CaLG06, respectively. The QTLs and linked markers identified in this study can be used in marker-assisted breeding for developing early maturing chickpea.